Consequences of environmental disaster in Kamchatka - Minchenko, O. V. (ТДАТУ, 2020)
There are many environmental problems in the modern world and the most global of them is happening now in Kamchatka. The Far Eastern piece of paradise on earth, the land of active volcanoes, bears and red fish, which managed to preserve the beauty of prehistoric nature on its territory, the abode of all kinds of flora and fauna listed in the World Red Book - the Kamchatka Peninsula is now experiencing the biggest environmental disaster associated with large-scale pollution water by an unknown chemical, which in the shortest possible time caused the death of almost 95% of the marine inhabitants of the coastal part of the Pacific Ocean near the Khalaktyr Beach.
Keywords: environmental problems in the modern world; humanity and the environment; insufficient information coverage